Praktik Kerjasama Usaha dalam Perspektif Musyarakah - Sup, Devid Frastiawan Amir; Masruri, Achmad Hasyim (Al Hikmah: Jurnal Studi Keislaman, 2023)
Abstract, Musyarakah is the concept of cooperation in an economic business based on sharia principles, which in this case uses a profit-sharing system, where profits and losses are share. There is a practice of collaboration with the name Pawon Emak As_Na with a business in the form of intestinal chips. This cooperation is carried out by two people. The two people agreed to collect capital to set up a business and the implementation of the business was carried out jointly, from the production process to marketing. This research aims to find out the mechanism of cooperative practice in the intestinal chips business at Pawon Emak As_Na and how this cooperation is practiced from a musyarakah perspective. This research is a qualitative research, descriptive, field research. The results of this research are that the mechanism of business cooperation practices at Pawon Emak As_Na is carried out by two people with the same portion of capital. Both of them are running their business, be it the search for raw materials, the production process, to marketing. The cooperation agreement is made verbally. Their principle is mutual trust because they already understand the character of each party. Then the practice of cooperating with intestinal chips at Pawon Emak As_Na in the musyarakah perspective is included in the uqud musyarakah, namely syirkah mufawadhah. The pillars and conditions of the musyarakah contract have been fulfilled, but ijab and qabul of their business cooperation are not strong, because the agreement has not been written so that if a conflict arises it can be denied by one of the parties. Keywords: Cooperation; Business; Musyarakah